ANALISA KERUSAKAN JALAN MENGGUNAKAN METODE SDI (STUDI KASUS RUAS JALAN DI KABUPATEN SUMBAWA): Road Damage Analysis Using SDI Method of Road Sections in Sumbawa District - Anwar Efendy; Cholid Zulfikan, Aan; Wahyuningsih, Titik; Isfanari, Isfanari; Sasmito, Sasmito; Wahyudi, Mudji; Fitrayudha, Adryan (Universitas Muhammadiyah Jember, 2024)
Roads have an important role in every regional development, especially in Sumbawa Regency. As many as 20 roads in Sumbawa Regency, specifically in Lopok District and Plampang District, were damaged due to repeated excessive traffic loads. This research aims to determine the level of damage to road conditions using the SDI (Surface Distress Index) method so that researchers can evaluate and find out what alternatives will be used to improve the condition of damaged roads. The results of the research are that STA 0+300 to 0+320 experienced serious damage, the type of treatment on this road section was road reconstruction. Meanwhile, STA 0+000 to 0+300, STA 0+320 to 0+500, and STA 0+760 to 0+800 experienced light damage, the type of treatment on these road sections was road rehabilitation. However, most of the roads in Lopok District and Plampang District, Sumbawa Regency are in good condition, seen at STA 0+500 to 0+760 and STA 0+800 to 1+100.